Catalytic Upgrading of Ethanol to n‐Butanol: Progress in Catalyst Development. Issue 1 (12th December 2017) - Wu, Xianyuan; Fang, Geqian; Tong, Yuqin; Jiang, Dahao; Liang, Zhe; Leng, Wenhua; Liu, Liu; Tu, Pengxiang; Wang, Hongjing; Ni, Jun; Li, Xiaonian
Abstract: Because n ‐butanol as a fuel additive has more advantageous physicochemical properties than those of ethanol, ethanol valorization to n ‐butanol through homo‐ or heterogeneous catalysis has received much attention in recent decades in both scientific and industrial fields. Recent progress in catalyst development for upgrading ethanol to n ‐butanol, which involves homogeneous catalysts, such as iridium and ruthenium complexes, and heterogeneous catalysts, including metal oxides, hydroxyapatite (HAP), and, in particular, supported metal catalysts, is reviewed herein. The structure–activity relationships of catalysts and underlying reaction mechanisms are critically examined, and future research directions on the design and improvement of catalysts are also proposed. Abstract : Fueling improvements : As a fuel additive, n ‐butanol has more advantageous physicochemical properties than those of ethanol, so ethanol valorization to n ‐butanol through homo‐ or heterogeneous catalysis has received much attention in recent decades. Recent progress in catalyst development for the upgrading of ethanol to n ‐butanol is reviewed, with special emphasis on the structure–activity relationships of catalysts and corresponding reaction mechanisms.